Testing of tomato hybrids of the breeding of the company "Gavrish" in JSC "Teplichnoye" of the Tambov region - Konstantin A. Chupkin; Vera I. Terekhova; Anastasiya V. Konstantinovich (Овощи России, 2019)
Relevance Currently, the requirements for modern tomato hybrids are increasing both from consumers and from producers. Modern tomato hybrids in extended circulation should yield at least 60 kg / m2, be distinguished by high quality of fruits, early ripeness, possess manufacturability, resistance to major diseases. Along with the traditional form of fruits, hybrids with original shape, color, taste and aroma are interesting for manufacturers. Methods The aim of the research was the variety study of indeterminant F1 hybrids of tomato breeding of the company "Gavrish" in JSC "Teplichnoye" of the Tambov region. Studies were conducted in 2017-2018 in the extended and summer-autumn turnover in the conditions of JSC "Teplichnoye" of the Tambov region in accordance with generally accepted recommendations for research with vegetable crops in greenhouses. The objects of the study in extended circulation were tomato hybrids: F1 Bao Bab, F1 Baloven, the F1 Torero hybrid was taken as a control. In the summerautumn turnover, a study was made of the rose hybrid – F1 Panthera; the Rosario F1 hybrid was used as a control; a hybrid with a plum-shaped fruit – F1 Armata, control – a hybrid F1 Lezghinka. Results According to the results of the study of tomato hybrids, the selection of the Gavrish company at the enterprise made the decision to grow it in extended circulation and increase the area under F1 Baloven, in the summer-autumn turnover under the F1 Panthera hybrid.